Forming ability of the WC-based ceramic metal composites with different Fe-based binders by unique laser beam modulation - H.S. Maurya; K. Juhani; F. Sergejev; R. Kumar; A. Hussain; K.G. Prashanth (Next Materials)
Additive manufacturing enables the production of cermet parts encompassing intricate geometries and tailored microstructures. The present study investigates the fabrication of WC-based Ceramic metal composites (CMC) with pure Fe and ferritic stainless steel (AISI Grade 430 L) green binders by controlling melt pool temperature during the Selective laser melting process. A study of crack restraining and formability of WC composite parts with different Fe-based binder compositions has been conducted by adapting Laser beam modulation (LBM). As a result of optimizing the laser beam with variations in laser power peaks (48, 60, and 72 Watt) and constant exposure times for each laser beam profile, the melt pool temperature was regulated, primary cracks in the parts were reduced and this resulted in the fabrication of the parts with reduced process defects such as internal thermal cracks. The reduction in cracks has been attributed to a lower thermal gradient, which has affected the microstructure and microhardness of the as-built parts. Scanning electron microscope (SEM) and X-ray diffraction (XRD) analysis have been used to study the microstructure and phase formation in the fabricated parts. The maximum microhardness (2048 ± 209 HV1) has been achieved for the fabricated cermets parts with ferritic stainless steel binder with the composition of WC-20 wt% FeCr.